2007
DOI: 10.1103/physrevlett.99.075002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Effects of Dust Particles on Plasma Fluctuation Spectra

Abstract: Charged dust particles are theoretically expected to modify the amplitude and spectrum of plasma fluctuations, and this can eventually provide novel diagnostic tools. Direct experimental evidence of the effects of dust particles on the fluctuations of a low collisionality plasma is reported, in agreement with the expectations of kinetic theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
21
1
Order By: Relevance
“…10,23 It is worth commenting on the difference between the present results and those previously published in Ref. 20. The qualitative picture of the phenomenon is preserved; the presence of dust does enhance the fluctuation power in the low-frequency range.…”
Section: Spectral Measurementscontrasting
confidence: 53%
See 3 more Smart Citations
“…10,23 It is worth commenting on the difference between the present results and those previously published in Ref. 20. The qualitative picture of the phenomenon is preserved; the presence of dust does enhance the fluctuation power in the low-frequency range.…”
Section: Spectral Measurementscontrasting
confidence: 53%
“…A wider frequency range of fluctuations previously observed is due to the different background plasma ͑"reference" spectra measured in dust free plasmas here and in Ref. 20 are not the same͒.…”
Section: Spectral Measurementsmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition, it was shown that the modification of the plasma fluctuation spectra due to the presence of dust, as predicted by the model, can be used as a diagnostic for sub-micron dust. 9,10 Typical laboratory complex plasmas are weakly ionized and collisions with neutrals are important for dust dynamics. An approach for the description of such a system has been proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%